Potent targeted larvicidal activities of marine-derived Bacillus sp. bacterial extracts on mosquito vectors - Cherish Prashar; Heena Devkar; Vandana Vandana; Madhavinadha P. Kona; Om P. Singh; Ram Das; Kapil Vashisht; Narsinh Thakur; Kailash C. Pandey (Scientific Reports)
Abstract Mosquito vector-borne diseases are one of the leading causes of mortality and morbidity across the globe. Current vector control strategies mainly rely on chemical insecticides, but their incessant usage has resulted in the development of resistance. Insecticidal agents of microbial origin have proven as good alternative tools for vector control of mosquito. In the present study, we examined larvicidal activities of the extracts from culture supernatants of marine bacteria (extracts) against major mosquito vectors from India. Out of 55 tested marine bacterial extracts, 12 extracts caused 90–100% mortality at 250 ppm in Anopheles stephensi larvae. Furthermore, NIO 707 and 706 were found to be significantly effective against Aedes aegypti larvae and field collected larvae of An. subpictus, respectively. Some of the extracts (NIO 701, 707 and 710) demonstrated significant reduction in egg hatching of An. stephensi; while all the tested extracts were able to significantly reduce egg hatching in An. culicifacies. Additionally, we observed that any of the effective extracts did not show any detrimental activity against malaria parasite (Plasmodium falciparum). Phylogenetic analysis revealed that most of the effective extracts belonged to Bacillus sp.; however, bacteria from Enterococcus genera was a peculiar finding of our study. Altogether, our data underscores the importance of exploration of marine bacteria from Indian peninsula for their larvicidal activities and further undertaking mechanistic approach to develop novel bio-larvicides.